Q-switching and mode-locking pulse generation in Ytterbium-doped fiber lasers using nanomaterial saturable absorbers / Ahmed Hasan Hamood al-Masoodi - Ahmed Hasan, Hamood al-Masoodi (2017)
This research work focuses on exploring various new nanomaterials for saturable absorber (SA) application in generating Q-switched and Mode-locked pulses operating at 1 μm region. These nanomaterials are Molybdenum disulfide (MoS2), Black Phosphorus (BP), Topological Insulator (TI): Bismuth (III) Selenide (Bi2Se3), Bismuth (III) Telluride (Bi2Te3), and antimony telluride (Sb2Te3), and metal oxide: Nickle Oxide (NiO) nanoparticles and cobalt oxide (Co3O4) nanocubes. The fiber laser employs Ytterbiumdoped fiber (YDF) as a gain medium. Firstly, molybdenum disulfide (MoS2) was proposed. The Q-switched laser was obtained by using few layers MoS2, which was mechanically exfoliated by using a scotch tape. The SA was sandwiched between two fiber ferrules to form a fiber compatible Q-switcher. By incorporating the SA inside the YDFL cavity, a stable pulse laser operating at 1070.2 nm wavelength was generated with the repetition rate was tunable from 3.817 to 25.25 kHz. A passively mode-locked YDFL was demonstrated using a few layered MoS2 film which was obtained by a liquid phase exfoliation technique. The mode-locking pulses have a repetition rate of 18.8 MHz and pulse energy of 0.1 nJ. Secondly, mechanically exfoliated Black phosphorus (BP) was proposed for both Q-switching and mode-locking pulses generation. The Q-switched laser has a pump threshold of 55.1 mW, a pulse repetition rate that is tunable from 8.2 to 32.9 kHz, the narrowest pulse width of 10.8 μs and the highest pulse energy of 328 nJ. BP based mode-locked YDFL was obtained by improving the SA preparation. The laser operated at 1033.76 nm with a fixed repetition rate of 10 MHz. Passively Q-switched YDFLs was also successfully demonstrated using a few-layers Bi2Se3, Bi2Te3 and antimony telluride (Sb2Te3) based SAs. For instance, a Sb2Te3 film based Q-switched YDFL produced pulse repetition rate, which was tunable from 24.4 to 55 kHz with the maximum pulse energy of 252.6 nJ at 82.3 mW pump power. The mode-locked YDFL operating at 24.2 MHz repetition and 18.8 ps pulse width were also realized with Sb2Te3 based SA. Finally, two transition metal oxide nanomaterials: Nickel Oxide (NiO) and cobalt oxide (Co3O4) were embedded into a polymer film, making it an SA device for both Q-switched and mode-locked YDFLs. Stable Q-switched and mode-locked YDFLs were realized with both materials. For instance, the mode-locked Co3O4 based YDFL was operated at 1035.8 nm wavelength with a fixed repetition rate of 20 MHz and picoseconds pulse width. In short, an efficient and low-cost Q-switched and mode-locked YDFLs operating in 1 μm region have been successfully achieved by utilizing various new nanomaterials as SA.